2006
DOI: 10.1063/1.2401651
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on Ar ion bombardment effects in amorphous SiO2 deposition processes

Abstract: Argon ion bombardment effects on growing amorphous SiO 2 films during reactive sputtering deposition processes were examined based on molecular dynamics ͑MD͒ and Monte Carlo ͑MC͒ simulation techniques. The system we have considered here is a film that is subject to energetic Ar bombardment while it is formed by surface reactions of Si and O atoms separately supplied at low kinetic energies. It has been found that ͑1͒ Ar injections preferentially sputter O atoms from the surface over Si and ͑2͒ also have a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…It is known that the native oxide at the Si bottom electrode of the pristine device is unstable owing to the ion bombardment effect by Ar plasma during the IGZO sputtering fabrication step. 56 As can be seen in Figure 4d, the Si−O peak at the bottom electrode is relatively high. This finding suggests that the bottom silicon oxide has a large Si dangling bond and that it is an insulating film.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…It is known that the native oxide at the Si bottom electrode of the pristine device is unstable owing to the ion bombardment effect by Ar plasma during the IGZO sputtering fabrication step. 56 As can be seen in Figure 4d, the Si−O peak at the bottom electrode is relatively high. This finding suggests that the bottom silicon oxide has a large Si dangling bond and that it is an insulating film.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…As mentioned earlier, this can be understood by seeing the tfMC simulation as conducting a random walk: each subsequent step is independent of the previous simulation steps. The timescale described by (6), however, assumes that the tfMC trajectory can be mapped onto a MD-like trajectory in which all steps are inherently correlated, contributing to one smooth trajectory. This assumption is closely tied to the suggestion of the tfMC authors that the method would be able to describe (approximate) system dynamics, which however cannot be achieved by a random walk.…”
Section: B Importance Ofmentioning
confidence: 99%
“…Indeed, it has been shown that the sequential application of MD and MMC allows an enhanced description of thin film growth, as evidenced by the higher quality of the obtained films that better match experimental results. [6][7][8][9] This comes at the cost of losing detailed information on the described physical timescale, of which only rough estimates are available. 8 Kikuchi et al 10,11 furthermore showed that MMC can be interpreted as a numerical solution of the Fokker-Planck equation and thus in principle has the ability to describe the true time evolution of Brownian diffusion processes.…”
Section: Introductionmentioning
confidence: 99%
“…17) and SiO 2 . 19 It has been shown that the higher the mass of the sputtered species, the lower will be its kinetic energy (size effect). 19 It has been shown that the higher the mass of the sputtered species, the lower will be its kinetic energy (size effect).…”
Section: The Model and Simulation Proceduresmentioning
confidence: 99%